Pengaruh Rasio Kemandirian Keuangan Terhadap Likuiditas dan Solvabilitas Pada Rumah Sakit Aloe Saboe - Ronal Idrus; Julie Abdullah; Onong Junus; Saprudin Saprudin; Mohamad Abdul Radjak Masjhur; Mega Nurannisa Hippy (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to analyze the effect of the financial independence ratio on liquidity and solvency at Aloe Saboe Hospital (RSAS) in Gorontalo City. As an institution implementing the Regional Public Service Agency Financial Management Pattern (PPK-BLUD), RSAS is required to improve financial performance and independence to provide top-notch public services without heavily relying on government funds. The research method used is a quantitative approach with secondary data analysis in the form of quarterly financial reports. Data analysis techniques include descriptive statistics, classical assumption tests, and hypothesis testing (t-test) using SPSS software. The results show that the independence ratio has a positive and significant effect on liquidity. This indicates that the higher the hospital's ability to generate independent revenue, The stronger the capacity to meet short-term obligations and routine operational costs, the better. Besides that, financial independence also positively affects solvency. These findings show that improving financial independence strengthens the hospital’s ability to cover all its obligations through its assets. In conclusion, financial independence is a crucial factor that determines the financial health of RSAS. Management is advised to keep optimizing BLUD’s own revenue to maintain liquidity and solvency stability for the continued delivery of healthcare services to the community.